The double witness : poems, 1970-1976 - Belitt, Ben, 1911-2003 (Princeton legacy library., 1977)
Ben Belitt writes, ""This volume-my fifth-extends and deepens a preoccupation I have had with the visible and invisible manifestations of people, places, and things. It offers a variety of poems of formal and textural density and, in addition, a system of 'doublings' and 'solitudes' whose oppositions express the drama of reality and appearance."" Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions pres